Spirituality in Coping with Infertility Stigma: A Mixed-Methods Study - Houndebasso-Ahoga, Jocelyne Annie; Wambugu, Anne Gathoni; Makena, Veronica Kaari (European Scientific Journal, ESJ, 2026)
Spirituality and religion are often involved in the coping approaches of women facing the psychosocial challenge of infertility in several African cultures. This convergent mixed-methods study examined the role of spirituality in coping with infertility-related stigma among 384 women attending evangelical churches in Zou County, Benin Republic. Data were collected using standardized instruments, the Assessment of Spirituality and Religious Sentiments (ASPIRES) and the COMPI Coping Strategy Scale (CSS), supplemented by focus groups and interviews with 45 church leaders. Quantitative data analysis was conducted using SPSS version 25.0, and a matched mixed-methods approach was used for the qualitative data analysis. Results indicated that the Spiritual Transcendence scale was dominated by the Prayer Fulfilment subscale, and the integration of qualitative findings confirmed a prayer-centred spirituality among the surveyed women. The analysis of the coping profiles indicated that the frequency of use was, respectively, active-confronting, meaning-based, passive-avoidance, and active-avoidance. In addition, the qualitative data revealed a three-stage coping trajectory: early-stage avoidance and shame; middle-stage indifference and adaptation; and late-stage meaning-based acceptance. Regarding spirituality in coping with infertility stigma, Spiritual Transcendence significantly predicted Coping Strategies, accounting for 20.3% of the variance. In line with the massive prevalence of prayer in the women’s management of infertility stigma, the high amount of unexplained variance suggests that spirituality is much more of a coping resource than a discrete strategy. The study contributes to understanding culturally situated coping mechanisms and informs interventions for mental health support in religious communities. Implications for clinical practice and church-based counselling are discussed.